2014
DOI: 10.1002/cpp.1905
|View full text |Cite
|
Sign up to set email alerts
|

Development of Measures to Assess Personal Recovery in Young People Treated in Specialist Mental Health Services

Abstract: BackgroundRecovery has become a central concept in mental health service-delivery and several recovery-focused measures exist for adults. The concept's applicability to young people's mental health experience has been neglected and no measures yet exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…Consistent with findings in the adult literature (Luo et al., ), the descriptive statistics indicated a difference between the mean scores obtained in this inpatient CAMHS sample on the ReQuest‐YP ( M = 30), and the mean score obtained in a community CAMHS sample on the ReQuest‐YP ( M = 43) as reported by John et al. (). This provides some support that the measure is able to discriminate between different populations.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Consistent with findings in the adult literature (Luo et al., ), the descriptive statistics indicated a difference between the mean scores obtained in this inpatient CAMHS sample on the ReQuest‐YP ( M = 30), and the mean score obtained in a community CAMHS sample on the ReQuest‐YP ( M = 43) as reported by John et al. (). This provides some support that the measure is able to discriminate between different populations.…”
Section: Discussionsupporting
confidence: 89%
“…John et al. () found that the measure showed sound psychometric properties in a community sample, including high internal consistency (Cronbach's alpha < .89). The measure correlated as expected with measures of similar constructs, including a measure of emotional and behavioural difficulties ( r = .74) and a measure of self‐esteem ( r = .84).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study provides insight into how adolescent users of mental health services experience their personal recovery and what they perceive as supportive and obstructive, a little researched topic (John et al, ; Mental Health Coordinating Council, ; Naughton et al, ; Palmquist et al, ; Ward, ). The results of this study indicate that the CHIME framework of Leamy et al (), which was used as the theoretical framework, was transferable to the personal recovery of the adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…First, clients' assessments of how and when change has occurred can differ from the view of therapists' or assessments by measures (Kazdin, ; Reese, Toland, & Hopkins, ). Second, there is continued debate about whether global and symptom‐based measures are sufficient to assess recovery (John, Jeffries, Acuna‐Rivera, Warren, & Simonds, ; Levitt, Butler, & Hill, ). Third, qualitative differences can be masked beneath quantitatively equivalent outcome findings (Klein & Elliott, ; Nilsson, Svensson, Sandell, & Clinton, ).…”
Section: Broadening the Assessment Of Effectivenessmentioning
confidence: 99%